Long-term safety and efficacy of rupatadine in Japanese patients with perennial allergic rhinitis: a 52-week open-label clinical trial - Okubo, Kimihiro (J Drug Assess, 2019)
Objective: Long-term safety and efficacy of 10- and 20-mg rupatadine in Japanese patients with perennial allergic rhinitis (PAR) were investigated in a 52-week open-label study (JapicCTI-152952, clinicaltrials.jp). Methods: The rupatadine dose was fixed to 10 mg once daily for the first 2 weeks. Thereafter, the study investigator was allowed to increase the dosage to 20 mg if the response was insufficient. Safety was evaluated on the basis of treatment-emergent adverse events, laboratory findings, and vital sign measurements. The primary efficacy endpoint was changed from baseline to Week 2 in the total 4 nasal symptom score. Secondary efficacy endpoints included changes over time in ocular symptoms, patient and physician clinical overall impression, and patient quality-of-life. Results: Seventy-two immunoglobulin E positive patients (mean age = 32.1 years), consisting of 58 adults (age ≥ 18 years) and 14 adolescents (12–17 years), were enrolled. Ninety-four treatment-emergent adverse events were reported in 48 patients (66.7%), including nine adverse drug reactions in nine patients (12.5%). The most frequently reported adverse drug reaction was somnolence (9.7%). The primary and secondary efficacy endpoints demonstrated a statistically significant clinical benefit with rupatadine. The rupatadine dose was increased from 10 to 20 mg in 36 patients (50.0%), which resulted in better symptom management. Conclusions: Rupatadine 10- and 20-mg once-daily doses were well tolerated in long-term use. Updosing to 20 mg is a reasonable option in PAR patients whose symptoms cannot be controlled effectively by the 10-mg dose.